RANCANG BANGUN APLIKASI PEMBELAJARAN SIRAH NABAWIYAH(PERJALANAN HIDUP ROSULULLAH) BERBASIS ANDROID (Information Technology and Telematics, 2013)
AbstractThe sophistication of the technology that is currently growing rapidly make smartphone function not only as a regular phone. But it can also help the user to perform learning easy,fast and precise. This is the background to create a learning system using Android-based mobile phone as a medium to provide easy alternative for Learning.This application is built using java, xml. Smartphones are used in this study is samsung galaxy young with system version android 2.2 (froyo/ froyen Yoghurt). Based system that has been created, the researcher can conclude, that the learning Sirah Nabawiyah (Perjalanan Hidup Rosululullah) Android-based learning can assist the user in making user Sirah Nabawiyah expected more active and diligent in learning.Keyword : Learning System, SirahNabawiyah,Mobile.